The Relationship Between International Students’ Health Perceptions and Their Healthy Lifestyle Behaviors - Citak Tunc, Gulseren (Journal of religion and health, 2021)
This study was carried out to examine the relationship between international students’ health perceptions and their healthy lifestyle behaviors. This descriptive and relational study was conducted with 216 international students studying at a university in Turkey. Study data were collected using the descriptive information form, the Perception of Health Scale (PHS) and the Health-Promoting Lifestyle Profile II (HPLP-II). Data were evaluated using descriptive statistics and Pearson correlation analysis. It was determined that the health perception and healthy lifestyle behaviors of the international students involved in this study were moderately positive. The study found a weak and positive relationship between PHS and the physical activity, nutrition and stress management subdimensions of HPLP, while a moderate positive relationship was identified between PHS and the spiritual growth and interpersonal relations subdimensions of HPLP. No relationship was observed between PHS and the health responsibility subdimension of HPLP. The fact that students have a positive perception of health reflects positively on their healthy lifestyle behaviors. It is important to disseminate education programs aimed at improving the health perception and healthy lifestyle behaviors of international students within the university.